2011
DOI: 10.3109/10715762.2011.579120
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporters affect the detection of intracellular oxidants by fluorescent probes

Abstract: Intracellular production of reactive oxygen species (ROS) plays an important role in the control of cell physiology. For the assessment of intracellular ROS production, a plethora of fluorescent probes is commonly used. Interestingly, chemical structures of these probes imply they could be substrates of plasma membrane efflux pumps, called ABC transporters. This study tested whether the determination of intracellular ROS production and mitochondrial membrane potential by selected fluorescent probes is modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Cytochrome c was added to the well 60 min before the end of the individual incubation period. The reduction was monitored as the cytochrome c absorbance at 550 nm increased (Prochazkova et al, 2011). Superoxide dismutase blocked the reduction of cytochrome c by 95-97%, which indicated that cytochrome c reduction was almost fully superoxide-dependent.…”
Section: Cytochrome C Reduction Assaymentioning
confidence: 99%
“…Cytochrome c was added to the well 60 min before the end of the individual incubation period. The reduction was monitored as the cytochrome c absorbance at 550 nm increased (Prochazkova et al, 2011). Superoxide dismutase blocked the reduction of cytochrome c by 95-97%, which indicated that cytochrome c reduction was almost fully superoxide-dependent.…”
Section: Cytochrome C Reduction Assaymentioning
confidence: 99%
“…U87 and U87-TxR cells were incubated overnight in adherent 6-well plates (100,000 cells/well). Then, cells were treated with protoflavones for 72 h. Cells were harvested by trypsinization and incubated in PBS with or without the P-gp inhibitor tariquidar (TQ) ranging concentration from 0.5 to 10 nM, in order to exclude the impact of P-gp transporter activity on DHR accumulation [21]. After 5 min, 1 µM DHR was added for another 30 min at 37 °C in the dark.…”
Section: Reactive Oxygen/nitrogen Species (Ros/rns) Detectionmentioning
confidence: 99%
“…Relative levels of proteins were quantified by scanning densitometry using the ImageJ™ program (National Institutes of Health, Bethesda, MD, USA), with the individual band density value expressed in arbitrary units (optical density, OD). An equal protein loading was verified by β-actin immunoblotting (Santa Cruz Biotechnology) [50]. The data in graphs represent the ratio between the individual values for OD of bands determined for phosphorylated, total form of protein or β-actin.…”
Section: Detection Of Protein Expression Using a Western Blot Techniquementioning
confidence: 99%